A case of urinary tract infection caused by Raoultella planticola after a urodynamic study - Tuğcu,Murat (2017)
Abstract Here we report the case of a patient who developed urinary tract infection after a urodynamic study. The causative agent was Raoultella planticola, a rare opportunistic pathogen that usually invades immunocompromised patients. While a urinary tract infection with R. planticola has been previously described, this is the first report in which an R. planticola infection developed after a urodynamic study. We postulate that the mechanism of infection was direct invasion of the urinary tract from contaminated urodynamic study equipment. Here, we discuss the role played by isotonic solutions in facilitating bacterial reproduction.